Implementasi Kebijakan Sistem Online Pembayaran dan Penyetoran Pajak Hotel dan Restoran dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Timor Tengah Utara - Fransiskus Xaverius Tabati; Yoakim Rembu; Nikolaus Uskono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Policy implementation is the process of running, implementing and pursuing policy decisions and their alternatives that have been decided in the hope of obtaining a result that is in accordance with the goals or objectives of a policy. This study aims to find out how the implementation of the online payment and payment system policy for hotel and restaurant taxes in increasing the original income of the North Central Timor Regency. This study uses a descriptive research method with a qualitative approach. The results of this study show that. The communication indicators carried out by the Regional Revenue Agency have been carried out in two stages directly and accepted by restaurant taxpayers while for hotels it has not been implemented, so it can be said that this policy has not been fully implemented. Then the indicators of resources in the Regional Revenue Agency are still very lacking, so it needs to be added again so that in carrying out the policy the tax online system is not gradual and can run optimally to help increase local revenue. The following are the indicators of disposition that exist in the Regional Revenue Agency has a good attitude and responsibility towards the policies they have implemented so far. And the last is the indicator of the bureaucratic structure that exists at the Regional Revenue Agency so far has carried out a good cooperative relationship between employees and related agencies in implementing the tax online system policy.